The Concept of Populist Economy based on Transcendental Law - Suci Hartati (IHSA Institute, 2021)
An economic system based on the paradigm of Pancasila values, placing people's sovereignty as the Khalifah of Allah SWT on the face of the earth, oriented towards the common good is what is meant by people's economy (economic democracy). There is a fundamental difference between the economic system in a country that adheres to liberal-capitalist democracy and socialist democracy. This people's economy is based on Pancasila and is an economy developed with a frame of spiritual values such as the value of God (Tauhid). The emergence of political investors whose interests are accommodated from the transactional system,